Raising Climate Heroes: Ecological Game Camp-A Mixed-Methods Study on Experiential Climate Education in Children and Adults - Demir Yildiz, Canan (Mdpi, 2025)
This mixed-method study explores the impact of the Raising Climate Heroes: Ecological Game Camp on climate change knowledge, awareness, behavior, and emotional engagement among primary school students and adult participants. Designed with experiential and game-based learning approaches, the program aimed to enhance environmental literacy through interactive, nature-centered activities. The quantitative findings from pre- and post-tests revealed significant increases in climate-related knowledge, awareness, climate-friendly behavior, hope, and reductions in climate anxiety. All measurement tools demonstrated high internal consistency (alpha = 0.809-0.914), indicating strong reliability across both age groups. Qualitative data, analyzed using descriptive thematic analysis, showed high levels of participant satisfaction. The adults emphasized educational gains, professional relevance, and appreciation of academic facilitation. The children focused on enjoyment, outdoor experiences, and social interaction. Activities such as ecological experiments, composting, and collaborative cooking were most favored. The results suggest that combining cognitive and emotional elements through play and hands-on learning can effectively promote pro-environmental attitudes. This study contributes to the literature by demonstrating how climate education can be both engaging and transformative for diverse learner groups.
Keywords: climate education; environmental awareness; experiential learning; eco-anxiety; game-based pedagogy; children and adults; sustainability education